Effects of short-term feeding with high fiber diets on growth, utilization of dietary fiber, and microbiota in pigs - Pu, Guang; Hou, Liming; Du, Taoran; Wang, Binbin; Liu, Hang; Li, Kaijun; Niu, Peipei; Zhou, Wuduo; Huang, Ruihua; Li, Pinghua (Frontiers in Microbiology, 2022)
Finishing pigs were found to be able to adapt to high fiber diet smoothly according to the production performance and their intestinal microbiota through a 28-day trial. However, it is unclear, at which stage during the experimental period, the adaptation occurred. Here we studied the dosage effects of dietary fiber (Total dietary fiber (TDF) from 16.70% to 24.11%) on growth performance, fiber digestibility, fecal microbiota and microbial fermentation of finishing pigs during a 14-day feeding period. The results showed that average daily feed intake (ADFI) and feed/gain (F/G) of pigs were not affected as the dietary fiber increased. Apparent total tract digestibility (ATTD) of cellulose, hemicellulose, insoluble dietary fiber (IDF), soluble dietary fiber (SDF) and TDF of pigs remained unchanged when TDF was between 16.70% and 17.75%, while strikingly decreased when TDF increased from 17.75% to 24.11%. It is worth noting that increasing of fiber intake seemed to favor hemicellulose digestion. In addition, the increase of fiber intake increased fecal microbial diversity, especially promoted the proliferation of the members of family Prevotellaceae, Ruminococcaceae and Lachnospiraceae, and decreased the abundance of the genus Streptococcus. Moreover, the increasing of fiber intake promoted the digestion of fiber, production of short chain fatty acids (SCFAs) and enhanced the microbial pyruvate metabolism and butanoate metabolism. In conclusion, short-term high fiber feeding has no adverse effects on growth performance of finishing pigs. ATTD of dietary fiber of finishing pigs were maintained when TDF was to 17.75%. And short-term high fiber feeding improved microbial diversity and fiber degradation functions of finishing pigs.